Khai phá mối quan hệ trao đổi lãnh đạo - nhân viên đến sự chia sẻ kiến thức và sự mâu thuẫn quan hệ với đồng nghiệp - Trần Mai , Đông; Nguyễn Thị Mai , Phương; Mai Trường , An; Nguyễn Thị Tuyết , Mai; Lý Thị Minh , Châu (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
This research aims to investigate the relationships between the leader - member exchange, the internal conflict and the knowledge sharing among employees, especially in the working environment of Eastern style. The current study employed qualitative research made by semi-structure interview method with sample size of 10 interviewees (experienced staffs, experts, and middle managers) to explore, deepen and sharpen their relationship quality of the leader -member exchange with superiors. The research findings made a contribution to the literature of the relationships among the leader - member exchange, emotional relationship conflicts at workplace and implicit knowledge sharing in the Vietnamese context where the gap between work and home is narrow; employees consider bosses as their relatives and bosses take care of employees as family members.
Keywords: The leader - member exchange; Implicit knowledge sharing; Relationship conflict; Eastern culture; Vietnam